International distance education at Tokyo Tech. - Nishihara, Akinori (Asean Engineering Journal)
This paper introduces distance education activities at Tokyo Institute of Technology. The Center for Research and Development of Educational Technology (CRADLE), being its key player, has been using commercial satellite, testbed network, and normal internet connections for international distance education. We have been conducting formal higher education at graduate level, and accumulated knowledge to improve the effectiveness of distance education, if not compatible to face to face education. Information and communication technology can further improve distance education by transmitting better quality video or by assisting teachers and learners using a learning management system and other useful tools.